THE PROBING-PROMPTING METHOD TO OVERCOME THE MONOTONOUS LEARNING PROCESS IN CLASS - Oktavianus Nunu Kodi (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2021)
The purpose of this study was to find out the learning process in the classroom through the probing-prompting method. In this study, the method used is a literature review which consists of four stages, namely collecting literature data, selecting relevant literature, conducting a review, and concluding or providing new interpretations. Data collection techniques are carried out online by downloading literature in the form of journals or articles through Google scholar with the keyword probing-prompting and obtained 113 literature data. The results of this literature study showed that the probing-prompting method in classroom learning was more effective than conventional learning methods. The Efforts made to achieve optimal learning in the classroom can be achieved through the foresight of teachers to choose learning methods that provide the space for students to participate actively, develop their potential. One of the better methods is the probing-prompting method. It can be seen from the development of student communication, increasing creative thinking, increasing critical thinking, instilling learning concepts, and improving the students’ learning outcomes.